Nin Jutsu: las escuelas tradicionales - Mauricio Martínez (Universidad de León, 2012)
José Manuel Collado Valencia. Madrid: Esteban Sanz Martínez, 1995. 369 páginas. 24x17 cm. I.S.B.N.: 987-84-85977-57-4.